Root-shoot ratio and its relationships with physiological characteristics, growth and biomass yield of Gynura procumbens under different shade levels and plant density - Ali Ahmed, Omar; Mohammad Yusoff, Martini; Misran, Azizah; Megat Wahab, Puteri Edaroyati; Abdualhamza Muttaleb, Qusay (Clinical Biotec, 2024)
Gynura procumbens is one of the most common medicinal plants in the Asteraceae family and has extensive pharmacological properties. The experiment was conducted to evaluate the effects of different shade levels (0 and 30% shade) and plant density (9, 15, and 25 plants m-2) on root-shoot ratio and it is a relationship with physiology, growth, and biomass yield using split-plot design with three replications. Increasing shade level to 30% shade significantly decreased root-shoot ratio (RSR) by22.54%, while total leaf dry weight per plant (TLDW) and total leaf dry weight per square meter (TLDW m-2) increased by 35.64, 11.58, and 32.18%, respectively due to negative correlation with RSR. Increasing plant density from 9 to 25 plants m-2 signifi- cantly increased RSR and TLDW m-2 by 67.71 and 18.54%, respectively, while TLDW decreased by 57.31%. There was a negative correlation between RSR and biomass yield per plant. Under stressed conditions (full sunlight and high plant density), G. procumbent plants appeared to change their strategy to absorb limited resources, allocate more biomass to the root system, and reduce the size of the aboveground parts to survive, resulting in high RSR.